Chitosan water-based binder for silicon negative electrode of lithium ion battery and preparation method of chitosan water-based binder

By using a modified chitosan water-based binder, the problems of unstable and insufficient bonding performance of silicon negative electrode binder in the prior art are solved, and high cycle stability and safety of lithium-ion batteries are achieved.

CN119799223AActive Publication Date: 2025-04-11ZHEJIANG CASNOVO MATERIALS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510297717.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-11
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

The silicon negative electrode binder of existing lithium-ion batteries is unstable in an aqueous environment and has insufficient bonding performance, making it difficult to effectively stabilize the volume changes and electrode structure of the silicon negative electrode.

Method used

Chitosan is used as the main body to prepare raw materials, and the chitosan binder is modified through the compounding and cross-linking reaction of acrylic monomer and polyol acrylate to form a composite binder with excellent bonding properties and water stability.

Benefits of technology

The cycle stability and safety of the silicon negative electrode of lithium-ion batteries is significantly improved, the conductivity and output power of the electrode material are enhanced, and the battery performance is optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799223A_ABST
    Figure CN119799223A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of binders, and particularly relates to a chitosan water-based binder for a silicon negative electrode of a lithium ion battery and a preparation method of the chitosan water-based binder. The chitosan water-based adhesive for the silicon negative electrode of the lithium ion battery is prepared from the following raw materials: chitosan, an acrylic monomer, acrylic polyol ester, a pH regulator, an initiator and deionized water, wherein the mass ratio of the chitosan to the acrylic monomer to the acrylic polyol ester is (10-15): (5-10): (1-3). The acrylic monomer and the acrylic polyol ester are used for modifying the chitosan, the prepared water-based adhesive has excellent adhesive performance, the peel strength can reach 12 N / m or above, and the water-based adhesive is particularly suitable for a silicon negative electrode of a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of binders, and specifically relates to a chitosan aqueous binder for a lithium ion battery silicon negative electrode and a preparation method thereof. Background Art

[0002] Lithium-ion batteries (LiBs) have been widely used in electric vehicles, portable electronic devices, and large-scale energy storage systems due to their high energy density. Among them, silicon anodes are regarded as key materials for improving the performance of lithium-ion batteries. Compared with the currently widely used graphite anodes, the theoretical specific capacity of silicon anodes is several times that of graphite. Therefore, at the same weight or volume, silicon anodes can store more energy, thereby further improving the battery's endurance. In addition, silicon, as an element with abundant reserves in the earth's crust, is not only widely available, but also low in cost. The use of silicon anodes can effectively reduce the cost of battery production. At the same time, the low potential characteristics of the silicon anode enable the battery to release more energy during the charging and discharging process, thereby further improving the overall energy density of the battery.

[0003] However, during the lithiation process of silicon anode, silicon particles will undergo a dramatic volume expansion (up to 300%), which may cause damage to the electrode structure, such as crack formation and active material shedding. These problems will not only reduce the cycle stability of the battery and shorten the battery life, but may also cause safety issues. Therefore, how to effectively stabilize the volume change of silicon anode, maintain the integrity of the electrode structure, and select a suitable binder has become the focus of current research.

[0004] Silicon negative electrode binders need to have high strength and high toughness, and be able to provide effective support and buffering when the volume of silicon particles changes to prevent damage to the electrode structure. At the same time, the binder must also have good electrochemical stability to avoid side reactions during battery charging and discharging, which affects battery performance. In addition, good compatibility with silicon negative electrode materials is also the key to ensuring the stability of the binder. In recent years, a variety of new binder materials have emerged, such as polymer-based binders, inorganic nanoparticle composite binders, and smart binders with self-healing functions. For example, Chinese patent CN116072878B discloses a binder for electrodes, the raw materials for its preparation include chitosan, butyl acrylate and methyl methacrylate. Although the binder has a high bonding strength, an acetic acid aqueous solution is required in its preparation process, and butyl acrylate and methyl methacrylate are mainly oily substances, which are difficult to work stably in an aqueous environment.

[0005] Therefore, the development of an aqueous binder for silicon negative electrode that can work stably in an aqueous environment and has excellent bonding properties has important research value and application prospects. Summary of the invention

[0006] In order to solve the above technical problems, the first aspect of the present invention provides a chitosan aqueous binder for lithium ion battery silicon negative electrode, and its preparation raw materials include: chitosan, acrylic acid monomer, acrylic acid polyol ester, pH regulator, initiator and deionized water.

[0007] As an implementable case, the mass ratio of chitosan, acrylic acid monomer, acrylic acid polyol ester and deionized water is (10-15): (5-10): (1-3): (72-84).

[0008] As an practicable case, the deacetylation degree of the chitosan is greater than 85%.

[0009] Furthermore, the chitosan is industrial chitosan purchased from Zhejiang Jinke Pharmaceutical Co., Ltd.

[0010] Chitosan, as a natural polysaccharide, has excellent film-forming and adhesive properties. It can be tightly combined with silicon negative electrode materials to form a stable structure, effectively reducing the deformation and rupture of electrode materials during charging and discharging, and significantly improving the cycle stability and safety of the battery. Its inherent conductivity can further enhance the conductivity of the electrode material after being compounded with the electrode material, thereby improving the output power and energy density of the battery and comprehensively optimizing the battery performance. In addition, chitosan also has good water absorption and tissue compatibility, which helps to promote the compatibility of electrodes and electrolytes, and forms a stable film to effectively block the interaction between the solution and solid materials in the electrolyte, further enhancing the cycle stability and safety of lithium batteries; however, the bonding performance of single-component chitosan is limited and requires further modification.

[0011] As an implementable example, the acrylic monomer includes: acrylic acid and / or methacrylic acid.

[0012] As an implementable case, the acrylic polyol ester includes one or more of pentaerythritol triacrylate, pentaerythritol trimethacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, glycerol trimethacrylate, and glycerol triacrylate.

[0013] The carboxyl functional group contained in the acrylic acid monomer molecule can undergo an esterification reaction with the hydroxyl group in the chitosan molecule to form an ester bond. The formation of the ester bond mainly enhances the chemical stability of chitosan. Acrylic acid polyol esters (such as pentaerythritol triacrylate, pentaerythritol tetraacrylate, and glycerol triacrylate) not only have multiple acrylate groups that can further participate in crosslinking or polymerization, but also the hydroxyl groups on their side chains help to improve the polarity of the molecule. When acrylic acid monomers are used in combination with acrylic acid polyol esters, they can jointly modify chitosan by crosslinking reaction. The combined system not only introduces functional groups of acrylate groups and hydroxyl groups, which can further enhance the adhesion and mechanical properties of chitosan, and may improve conductivity through structural optimization and other methods; and due to the hydroxyl group effect of acrylic acid polyol esters, the modified chitosan binder has better water properties, so it can work stably in an aqueous environment.

[0014] As an implementable case, the initiator is a peroxide initiator.

[0015] Furthermore, the peroxide initiator includes: one or more of ammonium persulfate, potassium persulfate, sodium persulfate, benzoyl peroxide, lauroyl peroxide, di-tert-butyl peroxide, diisopropyl peroxide, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, tert-butyl perbenzoate, isopropyl hydroperoxide, and tert-butyl hydroperoxide.

[0016] Furthermore, the initiator includes: one of ammonium persulfate, potassium persulfate, and sodium persulfate.

[0017] As an implementable case, the pH adjuster includes: one of sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, sodium carbonate aqueous solution, sodium bicarbonate aqueous solution, and ammonia water.

[0018] As an implementable case, the mass concentration of the sodium hydroxide aqueous solution is 1-3 wt%.

[0019] The second aspect of the present invention provides a method for preparing a chitosan aqueous binder for a lithium ion battery silicon negative electrode, comprising: S1. Add chitosan and acrylic acid monomer into deionized water, stir until chitosan is completely dissolved, then add acrylic acid polyol ester and initiator, and pass inert gas for 30-60 min; then heat the system to 45-55 °C and perform polymerization reaction for 5-8h; S2. After the reaction is completed, the system temperature is lowered to 20-30°C, and the system is neutralized to a pH of 6.5-7.5 with a pH adjuster, and then diluted with deionized water to a solid content of 3-8%, and stirred evenly to obtain a chitosan aqueous binder for lithium ion battery silicon negative electrode.

[0020] As an implementable example, the inert gas includes nitrogen.

[0021] Beneficial Effects (i) The present invention selects chitosan as the main raw material for preparing the binder, which can ensure that the product has certain bonding properties. The three-dimensional network structure prepared by modifying chitosan makes the binder have stronger adhesion, better anchors the silicon particles, and improves the stability of the negative electrode structure.

[0022] (ii) The present invention selects acrylic acid monomer and acrylic acid polyol ester to modify chitosan. The three components can further improve the bonding performance of the product through cross-linking polymerization reaction, and the peel strength can reach more than 12 N / m.

[0023] (III) The present invention further defines the mass ratio of chitosan, acrylic acid monomer, acrylic acid polyol ester and deionized water in the preparation raw materials as (10-15): (5-10): (1-3): (72-84), which can prepare a lithium-ion battery silicon negative electrode binder with excellent performance, and the binder has the possibility of being used in an aqueous environment.

[0024] (IV) The binder provided by the present invention is a water-based binder. The raw materials for its preparation do not include organic solvents. The product system is relatively environmentally friendly and the preparation process is relatively simple. The raw materials only need to be added in a certain order, stirred, and reacted. In addition, the source of the raw materials is relatively wide, the cost is relatively low, the product has excellent performance, and is particularly suitable for use in silicon negative electrodes of lithium-ion batteries.

[0025] (V) Currently, the binders commonly used in lithium-ion battery silicon negative electrodes on the market are mostly prepared with SBR and CMC as raw materials, but the bonding performance is average. The present invention provides a new type of chitosan aqueous binder for lithium-ion battery silicon negative electrodes, which has more excellent bonding performance and is a significant improvement compared to the existing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the peel strength of the chitosan aqueous binder for the lithium ion battery silicon negative electrode prepared in Example 1. DETAILED DESCRIPTION

[0027] Example 1 The first aspect of this example provides a chitosan aqueous binder for a lithium-ion battery silicon negative electrode. The raw materials for its preparation are, by mass, 150 g chitosan, 100 g acrylic acid, 30 g pentaerythritol tetraacrylate, 2.8 g ammonium persulfate, 2778 g sodium hydroxide aqueous solution with a mass concentration of 2 wt% and 3706 g deionized water.

[0028] The chitosan has a deacetylation degree greater than 85% and is industrial chitosan purchased from Zhejiang Golden Shell Pharmaceutical Co., Ltd.

[0029] The second aspect of this example provides a method for preparing a chitosan aqueous binder for a lithium ion battery silicon negative electrode, specifically: S1. According to the mass, 150 g chitosan and 100 g acrylic acid were added to 720 g deionized water, and the mixture was stirred until the chitosan was completely dissolved. Then, 30 g pentaerythritol tetraacrylate and 2.8 g ammonium persulfate were added, and nitrogen gas at 0.1 MPa was introduced for 30 min. Then, the system was heated to 45 °C and the polymerization reaction was carried out for 5 h. S2. After the reaction is completed, the system is cooled to 25 °C, and the system is neutralized to a pH of 7.0 with 2778 g of a 2 wt% sodium hydroxide aqueous solution, and then 2986 g of deionized water is added to dilute it to a solid content of 5 wt%, and stirred evenly to obtain a chitosan aqueous binder for lithium ion battery silicon negative electrode.

[0030] The schematic diagram of the peel strength of the chitosan aqueous binder for lithium ion battery silicon negative electrode prepared in this example is as follows Figure 1 As shown; a total of 2 tests were conducted, and the average of the 2 tests was taken as the final result.

[0031] Example 2 The first aspect of this example provides a chitosan aqueous binder for a lithium-ion battery silicon negative electrode. The raw materials for its preparation are, by mass, 100 g chitosan, 70 g acrylic acid, 20 g triacrylate, 1.9 g ammonium persulfate, 2778 g of a 2 wt% sodium hydroxide aqueous solution, and 3646 g deionized water.

[0032] The chitosan has a deacetylation degree greater than 85%, is industrial chitosan, and is purchased from Zhejiang Jinke Pharmaceutical Co., Ltd.

[0033] The second aspect of this example provides a method for preparing a chitosan aqueous binder for a lithium ion battery silicon negative electrode, specifically: S1. According to the mass, 100 g chitosan and 70 g acrylic acid were added to 810 g deionized water, and the mixture was stirred until the chitosan was completely dissolved. Then, 20 g triacrylate and 1.9 g ammonium persulfate were added, and nitrogen gas at 0.1 MPa was introduced for 30 min. Then, the system was heated to 50 °C and the polymerization reaction was carried out for 5 h. S2. After the reaction is completed, the system is cooled to 25 °C, and the system is neutralized to a pH of 7.0 with 2778 g of a 2 wt% sodium hydroxide aqueous solution, and then 2836 g of deionized water is added to dilute the mixture to a solid content of 5 wt%, and stirred evenly to obtain a chitosan aqueous binder for a lithium ion battery silicon negative electrode.

[0034] Example 3 The first aspect of this example provides a chitosan aqueous binder for a lithium-ion battery silicon negative electrode. The raw materials for its preparation are, by mass, 120 g chitosan, 60 g acrylic acid, 10 g pentaerythritol triacrylate, 1.9 g ammonium persulfate, 1660 g sodium hydroxide aqueous solution with a mass concentration of 2 wt% and 2694 g deionized water.

[0035] The chitosan has a deacetylation degree greater than 85%, is industrial chitosan, and is purchased from Zhejiang Jinke Pharmaceutical Co., Ltd.

[0036] The second aspect of this example provides a method for preparing a chitosan aqueous binder for a lithium ion battery silicon negative electrode, specifically: S1. According to the mass, 120 g chitosan and 60 g acrylic acid were added to 810 g deionized water, and the mixture was stirred until the chitosan was completely dissolved. Then, 10 g pentaerythritol triacrylate and 1.9 g ammonium persulfate were added, and nitrogen gas at 0.1 MPa was introduced for 30 min. Then, the system was heated to 55 °C and the polymerization reaction was carried out for 6 h. S2. After the reaction is completed, the system is cooled to 25 °C, and the system is neutralized to a pH of 7.0 with 1660 g of a 2 wt% sodium hydroxide aqueous solution, and then 1884 g of deionized water is added to dilute the solid content to 5 wt%, and stirred evenly to obtain a chitosan aqueous binder for lithium ion battery silicon negative electrode.

[0037] Example 4 The first aspect of this example provides a chitosan aqueous binder for a lithium-ion battery silicon negative electrode. The raw materials for its preparation are, by mass, 150 g chitosan, 50 g methacrylic acid, 10 g pentaerythritol tetraacrylate, 2.1 g ammonium persulfate, 775 g sodium hydroxide aqueous solution with a mass concentration of 3 wt% and 3820 g deionized water.

[0038] The chitosan has a deacetylation degree greater than 85%, is industrial chitosan, and is purchased from Zhejiang Jinke Pharmaceutical Co., Ltd.

[0039] The second aspect of this example provides a method for preparing a chitosan aqueous binder for a lithium ion battery silicon negative electrode, specifically: S1. According to the mass, 150 g chitosan and 50 g methacrylic acid were added to 790 g deionized water, and the mixture was stirred until the chitosan was completely dissolved. Then, 10 g pentaerythritol tetraacrylate and 2.1 g ammonium persulfate were added, and nitrogen gas at 0.1 MPa was introduced for 30 min. Then, the system was heated to 45 °C and the polymerization reaction was carried out for 7 h. S2. After the reaction is completed, the system is cooled to 25 °C, and the system is neutralized to a pH of 7.2 with 775 g of a 3 wt% sodium hydroxide aqueous solution, and then 3030 g of deionized water is added to dilute it to a solid content of 5 wt%, and stirred evenly to obtain a chitosan aqueous binder for lithium ion battery silicon negative electrode.

[0040] Example 5 The first aspect of this example provides a chitosan aqueous binder for a lithium-ion battery silicon negative electrode. The raw materials for its preparation are, by mass, 100 g chitosan, 50 g methacrylic acid, 15 g pentaerythritol tetraacrylate, 1.65 g ammonium persulfate, 465 g sodium hydroxide aqueous solution with a mass concentration of 5 wt% and 3166 g deionized water.

[0041] The chitosan has a deacetylation degree greater than 85%, is industrial chitosan, and is purchased from Zhejiang Jinke Pharmaceutical Co., Ltd.

[0042] The second aspect of this example provides a method for preparing a chitosan aqueous binder for a lithium ion battery silicon negative electrode, specifically: S1. According to the mass, 100 g chitosan and 50 g methacrylic acid were added to 835 g deionized water, and the mixture was stirred until the chitosan was completely dissolved. Then, 15 g pentaerythritol tetraacrylate and 1.65 g ammonium persulfate were added, and nitrogen gas at 0.1 MPa was introduced for 30 min. Then, the system was heated to 55 °C and the polymerization reaction was carried out for 8 h. S2. After the reaction is completed, the system is cooled to 25 °C, and the system is neutralized to a pH of 7.4 with 465 g of a 5 wt% sodium hydroxide aqueous solution, and then 2331 g of deionized water is added to dilute it to a solid content of 5 wt%, and stirred evenly to obtain a chitosan aqueous binder for lithium ion battery silicon negative electrode.

[0043] Comparative Example 1 This example provides a water-based binder. The raw materials for preparation include, by weight, 28 g of SBR (i.e., styrene-butadiene rubber, with a solid content of 50 wt%), 6 g of CMC (sodium carboxymethyl cellulose), and 420 g of deionized water.

[0044] The preparation method of the water-based binder is as follows: 28 g of SBR, 6 g of CMC and 420 g of deionized water are mixed and stirred at room temperature of 25°C to obtain the water-based binder.

[0045] The SBR and CMC were purchased from Guangzhou Songbai Chemical Co., Ltd.

[0046] Comparative Example 2 The specific implementation of this example is the same as that of Example 1, except that the raw materials for preparation in this example do not include pentaerythritol tetraacrylate.

[0047] Performance Testing 1. Peel strength test 300 g of the binder prepared in Examples 1-5 and Comparative Example 2 was diluted with 150 g of water, 5 g of conductive agent and 480 g of silicon-carbon material were added, and after complete infiltration, the mixture was dispersed at high speed for 4 h (rotation speed: linear speed 10 m / min), 65 g of deionized water was added to adjust the viscosity, and the prepared slurry was coated on copper foil by a single-sided intermittent coating machine and baked, and then coated (single-sided coating, surface density 0.95 g / dm 2 ), the coated electrode is placed in a 120 ℃ oven to dry for 12 hours, the dried electrode is rolled and cut, and the adhesive 180° peel strength test method in GB / T 2790-1995 is used for measurement.

[0048] Specific test method for comparative example 1: 5 g of conductive agent and 475 g of silicon-carbon material were added to 482 g of the binder of comparative example 1, and the raw materials were dispersed at high speed for 4 h (rotation speed: linear speed 10 m / min) after being completely infiltrated, and then 76 g of deionized water was added to adjust the viscosity, and the prepared slurry was coated on the copper foil through a single-sided intermittent coating machine and baked, and then coated (single-sided coating, surface density 0.95 g / dm 2 ), the coated electrode is placed in a 120 ℃ oven to dry for 12 hours, the dried electrode is rolled and cut, and the adhesive 180° peel strength test method in GB / T 2790-1995 is used for measurement.

[0049] The model of the above-mentioned conductive agent is Super P, purchased from Shanghai Huiping New Energy Co., Ltd.; the model of the silicon-carbon material is BSHC-300, purchased from Beite New Materials Group Co., Ltd.

[0050] The test results are detailed in Figure 1 and Table 1.

[0051] Table 1

[0052] The peel strength of Example 1 is the average value of 2 tests, and the specific peel strength test results correspond to Table 2.

[0053] Table 2

[0054] Among them, serial number 1 represents Figure 1 The red line data in .

[0055] Number 2 represents Figure 1 The green line data in .

[0056] It can be seen from the test results of the above Examples 1-5 that the peel strength of the water-based adhesive prepared by the present invention is above 12 N / m, while the peel strength of the water-based adhesive prepared by compounding SBR and CMC in the prior art is significantly lower than that of the product provided by the present invention; in addition, it can be seen from Comparative Example 2 that not adding acrylic polyol ester also has a significant negative impact on the bonding performance of the water-based adhesive.

Claims

1. A chitosan aqueous binder for lithium ion battery silicon negative electrode, characterized in that: The preparation raw materials include: chitosan, acrylic acid monomer, acrylic acid polyol ester, pH regulator, initiator and deionized water; The mass ratio of chitosan, acrylic acid monomer, acrylic acid polyol ester and deionized water is (10-15): (5-10): (1-3): (72-84); The acrylic polyol ester includes one or more of pentaerythritol triacrylate, pentaerythritol trimethacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, glyceryl trimethacrylate and glyceryl triacrylate.

2. The chitosan aqueous binder for lithium ion battery silicon negative electrode according to claim 1, characterized in that: The deacetylation degree of the chitosan is greater than 85%.

3. The chitosan aqueous binder for lithium ion battery silicon negative electrode according to claim 1, characterized in that: The acrylic acid monomers include: acrylic acid and / or methacrylic acid.

4. The chitosan aqueous binder for lithium ion battery silicon negative electrode according to claim 1, characterized in that: The initiator is a peroxide initiator.

5. The chitosan aqueous binder for lithium ion battery silicon negative electrode according to claim 4, characterized in that: The peroxide initiator includes: one or more of ammonium persulfate, potassium persulfate, sodium persulfate, benzoyl peroxide, lauroyl peroxide, di-tert-butyl peroxide, diisopropyl peroxide, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, tert-butyl perbenzoate, isopropyl hydroperoxide, and tert-butyl hydroperoxide.

6. The chitosan aqueous binder for lithium ion battery silicon negative electrode according to claim 1, characterized in that: The pH regulator comprises: one of a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution, a sodium carbonate aqueous solution, a sodium bicarbonate aqueous solution, and ammonia water.

7. The chitosan aqueous binder for lithium ion battery silicon negative electrode according to claim 6, characterized in that: The mass concentration of the sodium hydroxide aqueous solution is 1-3 wt %.

8. A method for preparing a chitosan aqueous binder for a lithium ion battery silicon negative electrode according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Add chitosan and acrylic acid monomer into deionized water, stir until chitosan is completely dissolved, then add acrylic acid polyol ester and initiator, and pass inert gas for 30-60 minutes; then heat the system to 45-55 °C to carry out polymerization reaction; S2. After the reaction is completed, the system temperature is lowered to 20-30°C, and the system is neutralized to a pH of 6.5-7.5 with a pH adjuster, and then diluted with deionized water to a solid content of 3-8%, and stirred evenly to obtain a chitosan aqueous binder for lithium ion battery silicon negative electrode.

9. The method for preparing the chitosan aqueous binder for lithium ion battery silicon negative electrode according to claim 8, characterized in that: The inert gas includes nitrogen.

10. The method for preparing the chitosan aqueous binder for lithium ion battery silicon negative electrode according to claim 8, characterized in that: The polymerization reaction time in step S1 is 5-8 hours.

Citation Information

Patent Citations

  • An electrode, its preparation method, and a lithium-ion battery

    CN116072878B

  • Charge modified chitosan cross-linked encapsulate

    CA3261675A1

  • Medicinal ultraviolet curing aqueous conductive pressure-sensitive adhesive

    CN107163866A

  • Water-based adhesive and preparation method thereof

    CN116694271A

  • UV-cured high-performance pressure-sensitive adhesive tape as well as preparation method and application thereof

    CN119019950A